Digital Literacy Emergency: The Effect of the use of Short Language on Students' Writing Skills - Latif, Abdul; Rofiq, Asngadi (Journal of Basic Education Research, 2025)
Purpose of the study: The digital literacy emergency has become a major concern in the world of education, especially in relation to the influence of the use of abbreviations on students' writing skills. Methodology: This study was conducted at Madrasah Tsanawiyah Al Amiriyah Banyuwangi, East Java, to identify how the habit of using abbreviations affects the quality of students' formal writing. Based on interviews and observations, it was found that 85% of students routinely use abbreviations in their written communication. This habit is considered to make the writing process easier and faster, but has a negative impact on aspects of formality and grammar. Main Findings: The data shows that the use of abbreviations is more dominant in less formal tasks such as essays (70%) than reports (60%) and formal letters (50%). The main factors driving this habit include academic pressure, the influence of social media, and the lack of emphasis on formal writing in the curriculum. This study highlights the need for an integrated learning strategy, combining traditional values ​​such as discipline in grammar with the use of digital technology. With a holistic curriculum approach, students are expected to be able to develop formal writing skills without sacrificing adaptation to modern technological developments. Novelty/Originality of this study: This research provides important innovations for educational policy makers to design learning methods that are relevant to the needs of the digital era while maintaining the quality of students' academic literacy.